Wandering Among Preschool Children with and Without Autism Spectrum Disorder. Issue 4 (May 2020) - Wiggins, Lisa D.; DiGuiseppi, Carolyn; Schieve, Laura; Moody, Eric; Soke, Gnakub; Giarelli, Ellen; Levy, Susan
ABSTRACT: Objectives: (1) Report the occurrence of wandering, or leaving a supervised space, among children with confirmed autism spectrum disorder (ASD), other developmental delay (DD) with a previous but unconfirmed ASD diagnosis (DDprevASD), DD without a previous ASD diagnosis, and a population comparison group (POP) at an age when wandering is no longer expected and (2) explore whether ASD status is associated with wandering independent of behavioral, developmental, and maternal factors. Method: Parents and children aged 4 to 5 years enrolled in the Study to Explore Early Development Phase-1+2. All children were screened for ASD symptoms upon enrollment. Those with ASD symptoms and/or a previous ASD diagnosis received the Mullen Scales of Early Learning (MSEL) to determine their developmental level and 2 ASD diagnostic tests to determine their ASD status. All other children were evaluated with the MSEL alone. Mothers completed the Child Behavior Checklist/1½-5, which includes an item on whether the child wanders away (categorized as at least sometimes true vs not true) and items assessing behavior problems. Results: Children with ASD (N = 1195) were significantly more likely to wander than children classified as DDprevASD (N = 230), DD (N = 1199), or POP (N = 1272) (60.4%, 41.3%, 22.3%, and 12.4%, respectively, p < 0.01). ASD status, very low developmental level, and affective, anxiety, attention, and oppositional problems were each independently associated with wandering behavior. Conclusion: Wandering is significantly more common among children with ASD and those with behavioral and developmental problems compared with other children. These findings can be used to increase the awareness of wandering among children with atypical development.